2017
DOI: 10.1145/3131276
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Authenticated Encryption--ASIC Designer’s Perspective

Abstract: Authenticated encryption (AE) has been a vital operation in cryptography due to its ability to provide confidentiality, integrity, and authenticity at the same time. Its use has soared in parallel with widespread use of the internet and has led to several new schemes. There have been studies investigating software performance of various schemes. However, the same is yet to be done for hardware. We present a comprehensive survey of hardware (specifically ASIC) performance of the most commonly used AE schemes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Past reviews of the area were also identified, such as [36,37,108,283]. However, they are limited in scope and the range of time covered.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Past reviews of the area were also identified, such as [36,37,108,283]. However, they are limited in scope and the range of time covered.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…In 2016, Abed et al [36] presented an extensive categorization of AE schemes proposed for the CAESAR competition schemes. Vizár [12] and Zhang et al [37] conducted similar studies on the CAESAR competition schemes. In 2017, Kavun et al [37] provided a hardware implementation benchmark for commonly used AE schemes that excluded a majority of schemes proposed in the CAESAR project.…”
Section: A Backgroundmentioning
confidence: 97%
See 2 more Smart Citations
“…The first group is a straightforward class called Encrypt-Then-MAC (ETM), which is designed and implemented by using both a hash function and a block cipher, e.g., the CBC-HMAC scheme [4] that is widespread used in IP security protocol suite IPSec and other applications [5]. The second group is composed of AE schemes based on block cipher, e.g., CCM, GCM, EAX, and OCB [6], and some of these schemes are even standardized or recommended by National Institute of Standards and Technology (NIST). The third group is the AE schemes based permutation [7], which were proposed and implemented with the appearance of Sponge functions, e.g., ASCON [8], PHOTON-Beetle [9], Oribatida [10], etc.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%